Mapping of quantitative trait loci for agronomic and morpho-physiological traits under drought environments in springbarley (Hordeum vulgare L.) - Sayed, Haitham; Al-Yassin, Adnan; Ceccarelli, Salvatore; Grando, Stefania; U. Stotz, Henrik; D. L. Fitt, Bruce; Baum, Michael (Blackwell Publishing, 2024)
Barley production is severely affected by drought caused by the unpredictable Medi-terranean weather patterns, which include uneven rainfall and extreme temperatures.This leads to a decrease in crop yield. However, to tackle this issue, landraces andwild species are crucial sources of variation for stress adaptive traits. By incorporat-ing these traits into improved varieties, we may see an increase in yield and stabilityunder drought conditions. Seventy-six quantitative traits loci (QTLs) identified traitswere mapped using recombinant inbred lines (RIL) population Arta Harmal-2//Esp/1808-4L, evaluated at six dry and semi-dry areas over 3 years. The study investi-gated traits such as grain yield, biological yield, harvest index, kernel weight, seed perhead, days to heading, kernel filling duration, growth vigour, growth habit, lodgingand plant height. Numerous QTLs were discovered that are associated with variousphenotypic traits related to grain yield, kernel yield, duration of filling period and daysto heading. For areas with less than 250 mm/annum of rainfall, QTLs were identifiedon chromosome 2H for biological yield, days to heading, and kernel weight, on 1Hfor harvest index, and on 2H, 4H, and 5H for kernel weight. For semi-dry areas withrainfall less than 450 mm, QTLs were found on chromosome 6H for grain yield, 2Hand 5H for kernel weight, 1H and 6H for seed per head, and 2H for days to heading.Notably, these QTLs significantly explain more than 10% of phenotypic variation.The 2H chromosome was found to have the most important QTL and pleiotropiceffect for yield and its components, such as kernel weight, days to heading, and bio-logical yield. The cross Arta/Harmal was adapted, and mechanisms were developedto cope with drought stress, reflected by the significant and positive correlation ofbiological yield and harvest index with grain yield. Chromosomes 1H, 2H, 4H and 5Hharbour more than 60% of mapped QTLs for dry areas. It is worth noting that theQTLs mentioned earlier, along with the kernel weight QTLs (QKW 1.5, QKW2.7b,QKW4.1, QKW6.7, QKW6.9), have consistently exhibited positive effects on cropyield in semi-dry and dry areas, making them potential candidates for breedingdrought-tolerant crops. Genomic co-localisation of the QTL for Arta/Harmal population suggested that selection for drought through linked markers can be anoption for drought tolerance selection for barley in dry areas.